I think is the top one!!!!!!!
Answer:
Make it an y=mx+b equation. -3y=-4x+12
Divide everything by -3
Answer is y=4/3x-4
Step-by-step explanation:
Answer:
g(x) - f(x) = -14x - 3
Step-by-step explanation:
We need to subtract the function f(x) = 9x + 4 from the function g(x) = -5 + 1. Rewriting these two functions in columns, we get
g(x)= -5x+1
- f(x) = -(9x+4) Note: Use parentheses as shown here.
--------------------
g(x) - f(x) = -14x - 3
Answer:
135
Step-by-step explanation:
Because the two vertical lines are parallel
that answer your question?
Step-by-step explanation:
hope it will help you...